Product Rule
posted by Irene on .
Can someone please help me with this?
f(x)=(x2)^1/2 * (x^23)^3 find f'(x) using the product rul.
This is what I came up with I just need to know if I did it right.
f'(x)=(x2)^1/2*3(x^23)+(x^23)^3*(1)^1/2
Hopefully I did. Thanks.
no. You are not using the chain rule..
If f(x)=g(x) * h(x) then
f'(x)=g(x) * h'(x) + g'(x) * h(x)
now if h(x)= (x2)^.5 then
h'(x) =.5 * (x2)^.5 *1
and if g(x)=(x^23)^3 then
g'(x)=3(x^23)^2 *(2x)
what is the product rule? Explain and provide an example
what is the product rule? Explain and provide an example

Please help me with dis problem....
Y=(25x)^2